THE OPPONENT THROUGH THE ANTI-VACCINATORS' EYES: THE LINGUISTIC DIMENSION OF THE MANIPULATIVE STRATEGY OF LABELLING - Сазонова, Ярослава (Taras Shevchenko National University of Kyiv (Ukraine), 2022)
Modern society is full of contradictions and struggles for public opinion, which creates preconditions for the use of a wide range of strategies, tactics and means of manipulation. The article focuses on the analysis of one of the manipulative strategies – "labelling" the opponent of political confrontation in order to emphasize its otherness and achieve certain political goals. The strategy and the verbal means of its expression aim at the speaker's selfapproval and self-expression of a certain ideology via humiliating others. The politicized topic of confrontation between vaccinators and anti-vaccinators is the matter of investigation, where the anti-vaccinators are marked as the group "we"; it allows a deeper understanding of its manipulative principles and cognitive differences with the group "others" as well as analyzing means of stipulating this confrontation. The first step of the investigation was to find out what subjective traits the anti-vaccinators saw in their opponents: it allowed to create a list of markers of the group "other" in contrast to the group "we" – anti-vaccinators. This list is a result of the analysis of discursive strategies of the opponent's dehumanization and demonization, i.e. of attributing him animalistic traits or traits of omnipotence and permissiveness that is difficult to overcome. As a result of lingual-pragmatic analysis, the structure of the group "others", their purpose and means of achieving it were identified. It was found out that the language and speech implementation of the strategy of "labelling" occurs at all levels: lexical, morphological, and syntactic. Cognitive associations implied in lexemes are widely used, which arouses the most uncivilized moods and contribute to inciting social tension, national intolerance, and so on. The analysis is based on modern Englishlanguage articles from publications in on-line media that adhere to professional ethics and journalistic standards.

Сучасне суспільство перенасичене протиріччями й боротьбою за суспільну думку, що створює передумови для використання широкого спектру стратегій, тактик і засобів маніпуляції. Увагу сфокусовано на аналізі однієї з маніпулятивних стратегій – "навішуванні ярликів" на опонента політичного протистояння задля підкреслення його інакшості й досягнення поставлених цілей. Ця стратегія й мовленнєві засоби її вираження спрямовані на самоствердження та самовираження певної ідеології шляхом приниження інших. Для вивчення було обрано політизовану тему протистояння вакцинаторів і антивакцінаторів, де останні окреслені як група "ми", що дозволяє глибше зрозуміти маніпулятивні засади, когнітивні розбіжності з групою "інші" й засоби омовлення цього протистояння. Першим кроком було з'ясувати, якими суб'єктивними рисами наділили прихильників вакцинації її опоненти, що дозволило створити перелік маркерів групи "інший" на відміну від групи "ми" – антивакцинаторів. Такий перелік можливий як наслідок аналізу дискурсивних стратегій дегуманізації і демонізації опонента, тобто приписування йому анімалістичних рис або рис усевладності й уседозволеності, сили, яку важко побороти. Унаслідок лінгвопрагматичного аналізу було виділено структуру групи "інші", їхню мету й засоби її досягнення з погляду антивакцинаторів (група "ми"). Було встановлено, що мовна й мовленнєва реалізації стратегії "навішування ярликів" відбувається на всіх рівнях: лексичному, морфологічному, синтаксичному. Широко використовуються когнітивні асоціації, імпліковані в лексемах, що збуджує найбільш нецивілізовані настрої, які сприяють підбурюванню соціальної напруги, роздмухують національну нетерпимість тощо. Аналіз проведено на матеріалі сучасних англомовних статей із видань, які дотримуються професійної етики й журналістських стандартів.
ОПОНЕНТ ОЧИМА АНТИВАКЦИНАТОРІВ: ЛІНГВІСТИЧНИЙ ВИМІР МАНІПУЛЯТИВНОЇ СТРАТЕГІЇ НАВІШУВАННЯ ЯРЛИКІВ
Keywords: anti-vaccinators; labelling; manipulation; COVID-19; linguistic pragmatics; implication; антивакцинатори; навішування ярликів; маніпуляція; COVID-19; лінгвістична прагматика; імплікація